Environmentally friendly technology of pulverized coal ash and slag removal for thermal power plants - Gavlitin, N.V.; Messerle V.Е.; Ustimenko А.B.; Lavrischev О.А. (Recent Contributions to Physics, 2012)
The technology transfer to dry ash removal of Reftinskaya TPP maintaining hydraulic slag removal, which will allow storage of ash materials in the existing area by high-loaded scheme for sailing without removal of large areas of the construction of a new ash disposal. Reconstruction of the power plant ash removal and the transition to modern dry technology and a significant reduction in the amount of material transported by the ash dump the hydraulic method, reduces technical and clarified water. The need for technical and clarified water at the joint hydraulic removal of ash and slag is about 9500 t/h, including technical 2750 t/h In the dry method for removing ash and hydraulic removal of slag and ash from a boiler in need of technical and clarified water is 1986.3 t/h, including technical - 238.7 t/h The economic effect of the reconstruction of ash removal and transfer it to the dry method, will be about 300 million rubles. a year just by reducing operating costs. Reducing damage to the environment from coal-fired generation can be achieved by switching to cleaner fuels, coal origin and its utilization of technology, for example, with the use of plasma technology for complex processing of high-ash coal.